Pengaruh Kualitas Pelayanan, Harga, dan Lokasi Terhadap Keputusan Menggunakan Jasa Service Mobil ( Studi Kasus pada Konsumen PT. Sun Star Motor Banyumanik Semarang) - Sebastian Mardeta Ferandi; Bulan Prabawani; Ngatno Ngatno (Universitas Diponegoro, 2016)
Sun Star Motor is a company engaged in the automotive field is a car dealer of Mitsubishi brand. PT. SunStar Motor Banyumanik Semarang has its own place in the hearts of the loyal customers. However, the advantagesoffered by this restaurant is considered suboptimal. Many of the complaints submitted by consumers among others,the parking area facilities, service quality, price, as well as other services are less than satisfactory for consumers.So it will obviously be able to influence purchasing decisions.The aims of this study was to determine the influence of service quality, price, and location oncustomers'decision to use car service in PT. Sun Star Motor Banyumanik Semarang. The type of this research wasexplanatory research. Population in this research were the customers of PT. Sun Star Motor Banyumanik Semarangand the number of samples were 100 respondents. The sampling technique in this study was using a non-probabilitysampling with purposive sampling technique. The analytical method used was cross tabulation, correlation,determination, simple linear regression, multiple, t test and F test with SPSS version 20.Based on the survey results revealed that the service quality, price, and location have a significant effect oncustomers'decisions to use service car, either partially or simultaneously. Independent variables that have thebiggest influence on purchasing decisions was the variable of location.The advice can be given that maintain and even improve the quality of quality service to always payattention to consumer needs and desires of diverse, maintaining price stability in order to keep consumers loyal,while maintaining access to the site in order to stay within easy reach of consumers, so that consumers do nottrouble to the location, as well as improving the overall service of other services that consumers find it appropriateto make a purchase decision, repurchase, and they can recommend this place to other people.